Decolonising the South African university: First thoughts - Hlatshwayo, M. (South African Journal of Higher Education, 2023)
Times are indeed changing as South African universities continues to struggle under the growing pressures and ethical demands for transformation and decolonisation. Underpinning these pressures and demands is the taken for granted assumption that all is not well in the South African academy, and that urgent structural and deep rooted changes are necessary. In this article, I foreground the emergent decolonial calls for transformation in the South African higher education. I rely on Le Grange (2019) and Hlatshwayo and Shawa (2020)’s notion of ubuntu currere to not only formulate theoretical and empirical critiques at the South African higher education system, but I also begin to offer some first thoughts on the solutions that could be enacted. I focus in particular on the (decolonial) purposes of a university as offering us a very useful space to reflect on and theorise the potential for decoloniality and transformative practices in the academy. I end the article with some conclusion and recommendations on the future of the academy in South Africa, and the projected nature of the struggles for transformation and decolonisation in the sector.